1991
DOI: 10.20506/rst.10.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Hépatites d'origine virale des léporidés : introduction et hypothèses étiologiques

Abstract: In less than ten years, two very serious viral hepatic diseases have spread through Leporidae populations (rabbits and hares) in numerous countries. In May 1989, the Office International des Epizooties designated this new disease of rabbits "viral haemorrhagic disease" and entered it as a List B disease in the International Animal Health Code. Clinically, the disease is very similar to the European brown hare syndrome. However, numerous uncertainties prevail today on the true nature of the viruses of the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(15 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…European scientists (Morisse et al 1991;Rodak et al 1991) reported that even in the absence of maternal antibodies, domestic rabbits younger than 4 weeks did not develop clinical signs or pathological lesions. Nevertheless, there was replication of the virus following infection and the young rabbits developed lifelong immunity.…”
Section: Response Of Immature Rabbits To Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…European scientists (Morisse et al 1991;Rodak et al 1991) reported that even in the absence of maternal antibodies, domestic rabbits younger than 4 weeks did not develop clinical signs or pathological lesions. Nevertheless, there was replication of the virus following infection and the young rabbits developed lifelong immunity.…”
Section: Response Of Immature Rabbits To Infectionmentioning
confidence: 99%
“…Nevertheless, a new disease -'Malattia-X' -was recognised among domestic rabbits in Italy in 1986 (Cancellotti and Renzi 1991) and soon appeared in other countries in Europe (Morisse et al 1991). This new disease was at first regarded as being due to a toxin, or to fallout from the Chernobyl disaster.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This disease was first reported in China in 1984, and has, since, spread rapidly around the world in less than 10 years, causing considerable economic losses in the rabbit industry and impacting the ecology of wild rabbit populations [1,2,5,6]. In 1989, OIE designated this illness as a viral hemorrhagic disease and added it to List B of the International Animal Health Code [7]. Subsequently, a novel lagovirus, GI.2, emerged in France in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is the main approach for controlling RHDV because no effective treatment is available for this disease. Inactivated vaccines against RHDV were introduced in the early 1990s, improving the survival of rabbits on rabbit farms [7,14]. However, RHDV inactivated vaccines are manufactured using the livers of rabbits infected with RHDV.…”
Section: Introductionmentioning
confidence: 99%